2020
DOI: 10.1101/2020.09.22.308700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting Allostery in the Dynein Motor Domain with Small Molecule Inhibitors

Abstract: Cytoplasmic dyneins are AAA (ATPase associated with diverse cellular activities) motor proteins responsible for microtubule minus-end-directed intracellular transport. Dynein's unusually large size, four distinct nucleotide-binding sites, and the existence of closely-related isoforms with different functions, pose challenges for the design of potent and selective chemical inhibitors. Here we use structural approaches to develop a model for the inhibition of a well-characterized S. cerevisiae dynein construct b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…New analogs of dynapyrazole, recently introduced by Santarossa et al, [36] have shown to be potent in inhibiting basal ATPase activity of dynein while binding to AAA3 and AAA4. The binding assessment of analogs 3-48 will be critical in evaluating their inhibitory mode of action at the AAA3 binding site, which is not conserved in axonemal dynein and cytoplasmic dynein 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New analogs of dynapyrazole, recently introduced by Santarossa et al, [36] have shown to be potent in inhibiting basal ATPase activity of dynein while binding to AAA3 and AAA4. The binding assessment of analogs 3-48 will be critical in evaluating their inhibitory mode of action at the AAA3 binding site, which is not conserved in axonemal dynein and cytoplasmic dynein 2.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown that ciliobrevin A and D, which bind to AAA1, might bind to the AAA3 site [10]. In contrast, analogs of dynapyrazole, especially compound 20, abolished basal dynein activity by binding to the AAA3 and AAA4 [36]. Forty-six (46) analogs of ciliobrevin A and D were proposed to have potentially higher selectivity and potency than ciliobrevin A against dynein 2 [7].…”
Section: 1mentioning
confidence: 99%